Effects of pseudoephedrine on parameters affecting exercise performance: a meta-analysis - Maria D Gheorghiev; Farzad Hosseini; Jason Moran; Chris E Cooper (SpringerOpen, 2018)
Abstract Background Pseudoephedrine (PSE), a sympathomimetic drug, commonly used in nasal decongestants, is currently banned in sports by the World Anti-Doping Agency (WADA), as its stimulant activity is claimed to enhance performance. This meta-analysis described the effects of PSE on factors relating to sport performance. Methods All included studies were randomised placebo-controlled trials and were conducted in a double blind crossover fashion. All participants (males and females) were deemed to be healthy. For the primary analysis, standardised mean difference effect sizes (ES) were calculated for heart rate (HR), time trial (TT) performance, rating of perceived exertion, blood glucose, and blood lactate. Results Across all parameters, effects were trivial with the exception of HR, which showed a small positive increase in favour of PSE ingestion (ES = 0.43; 95% confidence interval: − 0.01 to 0.88). However, subgroup analyses revealed important trends. Effect sizes for HR (increase) and TT (quicker) were larger in well-trained (VO2 max (maximal oxygen consumption) ≥ 65 ml/kg/min) and younger (< 28 years) participants, for shorter (< 25 mins) bouts of exercise and when PSE was administered less than 90 min prior to performance. There was evidence of a dose-response effect for TT and HR with larger doses (> 170 mg) resulting in small (ES = − 0.24) and moderate (ES = 0.85) effect sizes respectively for these variables. Conclusions We conclude, however, that the performance benefit of pseudoephedrine is marginal and likely to be less than that obtained from permitted stimulants such as caffeine.